Mesenchymal and haematopoietic stem cells form a unique bone marrow niche - Méndez-Ferrer, Simón; Michurina, Tatyana V.; Ferraro, Francesca; Mazloom, Amin R.; MacArthur, Ben D.; Lira, Sergio A.; Scadden, David T.; Ma’ayan, Avi; Enikolopov, Grigori N.; Frenette, Paul S. (Nature (London), 2010)
The cellular constituents forming the haematopoietic stem cell (HSC) niche in the bone marrow are unclear, with studies implicating osteoblasts, endothelial and perivascular cells. Here we demonstrate that mesenchymal stem cells (MSCs), identified using nestin expression, constitute an essential HSC niche component. Nestin + MSCs contain all the bone-marrow colony-forming-unit fibroblastic activity and can be propagated as non-adherent ‘mesenspheres’ that can self-renew and expand in serial transplantations. Nestin + MSCs are spatially associated with HSCs and adrenergic nerve fibres, and highly express HSC maintenance genes. These genes, and others triggering osteoblastic differentiation, are selectively downregulated during enforced HSC mobilization or β3 adrenoreceptor activation. Whereas parathormone administration doubles the number of bone marrow nestin + cells and favours their osteoblastic differentiation, in vivo nestin + cell depletion rapidly reduces HSC content in the bone marrow. Purified HSCs home near nestin + MSCs in the bone marrow of lethally irradiated mice, whereas in vivo nestin + cell depletion significantly reduces bone marrow homing of haematopoietic progenitors. These results uncover an unprecedented partnership between two distinct somatic stem-cell types and are indicative of a unique niche in the bone marrow made of heterotypic stem-cell pairs. A stem-cell niche made for two The identity of the cells that form the haematopoietic stem-cell niche in the bone marrow has been unclear. Paul Frenette and colleagues have now identified nestin-expressing mesenchymal stem cells as niche-forming cells. These cells show a close physical association with haematopoietic stem cells, express high levels of genes involved in stem-cell maintenance, and their depletion reduces bone-marrow homing of haematopoietic progenitors. This work reveals the stem-cell niche in the bone marrow as a partnership between two distinct somatic stem-cell types. The identity of the cells that form the haematopoietic stem cell (HSC) niche in bone marrow has been unclear. These authors identify nestin-expressing mesenchymal stem cells as niche-forming cells. These nestin-expressing cells show a close physical association with HSCs and express high levels of genes involved in HSC maintenance, and their depletion reduces bone marrow homing of haematopoietic progenitors.